The impact of psoriatic arthritis on quality of life: a systematic review - James, L; Hailey, L; Suribhatia, R; McGagh, D; Amarnani, R; Bundy, C; Kirtley, S; O'Sullivan, D; Steinkoenig, I; White, J; Vivekanantham, A; Coates, LC (SAGE Publications, 2024)
Background: Psoriatic arthritis (PsA) is a chronic inflammatory condition that can affect individuals of all ages. Patients may experience a range of physical and psychological issues. Objective: To examine the impact of PsA on an individual’s quality of life (QoL) and physical function. Design: A systematic review of the literature. Data sources and methods: A comprehensive search was conducted across seven electronic databases (Cochrane Central Register of Controlled Trials (CENTRAL), CINAHL, AMED, EMBASE, Global Health, MEDLINE and PsycINFO) to retrieve articles related to QoL and lifestyle in adults with PsA. The inclusion criteria were studies published between 2010 and 2021 that used outcomes validated in patients with PsA. The methodological quality was assessed using Joanna Briggs Institute Critical Appraisal Tools. Our primary outcomes were patient-reported outcomes (PROs) measuring QoL and the impact of disease on physical function. The secondary outcomes were assessments of fatigue, anxiety, depression, sleep, work productivity and employment. Results: The study included 37 comprehensive studies that examined the impact of PsA on QoL and physical function. The findings revealed that the impact of PsA extends to various aspects of life, including activities of daily living, physical, and emotional aspects, such as fatigue, sleep disturbance, anxiety and depression. Notably, people with PsA experience reduced health-related quality of life (HRQoL), particularly in emotional, social and mental health aspects. The severity of pain and/or fatigue is directly linked to decreased HRQoL. Importantly, those who fail to achieve minimal disease activity face challenges in work productivity and employment status. Conclusion: To conclude, our review underscores the significant impact of PsA on patients’ HRQoL beyond joint disease. The emotional, social, and mental aspects of PsA require compassionate and holistic management. Trial registration: The PROSPERO international prospective register of systematic reviews – CRD42021257395.